Inovasi, Teknologi, dan Kepuasan Pelanggan: Kunci Keberhasilan UMKM di Pasar yang Kompetitif - Metris, Diksi; Rasyiddin, Ahmad; Sari Siahaan, Febri; Rayyani Aulia, Khansa; Rinjani Faatihah, Ananda (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
MSMEs (Micro, Small and Medium Enterprises) face big challenges in maintaining competitiveness amidst increasingly competitive market dynamics. The main problem faced is the low adoption of innovation and technology, which often impacts customer satisfaction levels. This research aims to understand the role of innovation and technology in increasing customer satisfaction as the key to the success of MSMEs. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with 20 MSME owners in the food and beverage sector as well as field observations of the operational and marketing strategies they implemented. Data analysis was carried out thematically to identify main patterns related to innovation, technology and their impact on customer satisfaction. The research results show that the application of digital technology, such as the use of e-commerce applications and social media for marketing, can significantly improve customer experience. In addition, innovation in the form of product development, service personalization, and more flexible interaction strategies has been proven to strengthen customer loyalty. The findings also show that MSME players who actively adapt to technological changes have greater opportunities to create added value for customers. This research concludes that innovation and technology play a crucial role in building strong relationships with customers and increasing their satisfaction. Recommendations are given to MSMEs to be more proactive in integrating technology into their business strategy and developing innovations that are relevant to market needs. This research also provides practical insights for policy makers in supporting the digital transformation of MSMEs.